A review of shipboard large-scale energy storage systems - Sidun FANG; Hongdong WANG; Junjun ZHANG (Zhongguo Jianchuan Yanjiu, 2022)
The energy storage system is an essential piece of equipment in a ship which can supply various kinds of shipboard loads. With the maturity of electric propulsion technology, all-electric ships have become the main trend of future ship design. In this context, instead of being mainly responsible for auxiliary loads as in the past, the energy storage system will be responsible for multiple types of ship loads, especially acting as a part of the ship's power system and cooperating with the ship's main/auxiliary engines to improve its economic/environmental characteristics. This change in role will accelerate the integration of large-scale energy storage systems into ships, bringing a series of issues such as energy storage system state estimation, energy management and optimization planning. This paper first classifies current energy storage technologies, then introduces the structures of typical all-electric ships and points out the application scenarios of energy storage systems, and finally proposes several technical problems that need to be resolved after large-capacity energy storage systems are connected to ships, namely the distributed control of ship energy storage systems, adaptive planning and optimization of ship energy storage systems, and state estimation of ship energy storage systems. This study clarifies the future roadmap for large-scale energy storage integration into electrified ships.